Standing Needle Arthroscopy of the Metacarpophalangeal and Metatarsophalangeal Joint for Removal of Dorsal Osteochondral Fragmentation in 21 Horses - Bonilla, Alvaro G. (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The aim of this study was to report the technique, experience and outcome of standing arthroscopic removal of dorsal osteochondral fragmentation of the metacarpophalangeal and metatarsophalangeal joint using a 1.2-mm needle arthroscope.Study Design This was a prospective clinical study.Materials and Methods All horses referred for standing arthroscopic removal of dorsoproximal first phalanx fragments or fragments embedded in the distal aspect of the synovial plica were included. Relevant information from the cases was recorded. Follow-up was obtained by a telephone questionnaire.Results Twenty-one horses with a mean age of 4.5 years old were included. Osteochondral fragments removed were from the proximal margin of first phalanx in 18 horses (24 joints), in the synovial plica in 2 horses (2 joints) or free-floating fragment in 1 horse (1 joint). Fifteen out of twenty-one horses were unilaterally affected and 6/21 bilaterally. Fifteen out of twenty-seven affected joints were forelimbs and 12/27 hindlimbs. All articular structures within the dorsal recess of the joint were visible. The arthroscope was deemed easy to use and manoeuvre. Only minor complications occurred during the procedure. Surgery time was 15 to 20 minutes for most patients.Conclusions All fragments were successfully removed and needle arthroscopy allowed a thorough evaluation of the dorsal aspect of the joint. The technique offers an alternative for standing fetlock arthroscopy for surgeons concerned about equipment damage or portability.
Keywords: equine; needle; standing; metacarpophalangeal joint; arthroscopy; minimally invasive; osteochondral fragment